2019
DOI: 10.1177/1527476419851081
|View full text |Cite
|
Sign up to set email alerts
|

Precarity and Why Indie Game Developers Can’t Save Us from Racism

Abstract: Exploring issues of labor and inequality at the intersection of AAA and indie sectors, this article interrogates the perception of the indie sector as key to mitigating the production of racializing or racist game content. As developers are central to the industry and the larger games culture, their views reveal how indies are imagined as a privileged site free from economic pressures where racism can be ameliorated. Based on interviews with developers, I argue that the project to redress representational ineq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In this, my analysis provides cultural-sociological and empirical support for Horkheimer and Adorno's concept of sameness -across at least one AAA example (Assassin's Creed in the previous chapter) and a broad selection of indies. Indeed, we can see similar observations elsewhere, namely a process of standardization under global capitalist "transnational cultural fields" (Kuipers, 2011, p. 555;Kline et al, 2003), especially with indies working under economic precarity (Lima, 2018;Srauy, 2019).…”
Section: Conclusion: Religious Values Become Commodified Signssupporting
confidence: 79%
See 1 more Smart Citation
“…In this, my analysis provides cultural-sociological and empirical support for Horkheimer and Adorno's concept of sameness -across at least one AAA example (Assassin's Creed in the previous chapter) and a broad selection of indies. Indeed, we can see similar observations elsewhere, namely a process of standardization under global capitalist "transnational cultural fields" (Kuipers, 2011, p. 555;Kline et al, 2003), especially with indies working under economic precarity (Lima, 2018;Srauy, 2019).…”
Section: Conclusion: Religious Values Become Commodified Signssupporting
confidence: 79%
“…While researchers have surveyed the religious affiliations of independent developers (Piasecki, 2016), their racial identities and attitudes (Srauy, 2019) and their gender representation in light of their economic independence (Lima, 2018), there is little insight into how religion is put into games by those who make them. More so, most studies on religion in games, as observed in the introduction (Chapter 1), are game-based interpretations.…”
mentioning
confidence: 99%
“…Studies of female characters in mainstream games have found these complexities that are often subverted in favor of game play, action sequences, or plot. In addition, in contrast, to the structural concerns regarding video games noted by Srauy (2019), the indie games in this sample provide positive deeper platforms to understand women and their involvement in fantasy world of games, as well as the realities they have faced. As a woman has the freedom to choose in game play, so does the female character have the opportunity to change their story into a deeply developed one, with facets beyond the bounds of traditional video game storytelling.…”
Section: Discussionmentioning
confidence: 79%
“…Stories are retold in new ways, using new media-and therefore, the stories told in video games are no different (Bascom, 1965). Narrative theory helps identify how applying previous contexts to culturally ingrained stories can help explain what is happening in society (Chess, 2016;Perreault & Paul, 2018, 2019. Therefore, we will use narrative theory as a theoretical lens to examine the ways women are presented in these three games, released around the GamerGate controversy.…”
Section: Video Game Narrativesmentioning
confidence: 99%
“…An issue that requires further analysis is how indie developers are offloaded the task to resolve racial inequalities in the broader gaming ecosystem. The framing of the independent game sector as a remedy to racist game content only increases the emotional labor undertaken by indie game developers (Ruberg, 2019; Srauy, 2019). At the same time, indie games’ progressive potentials create new multicultural markets that are ready to capture indie developers’ labor power.…”
Section: White Masculinity Ideology and Technological Practice In Gmentioning
confidence: 99%